The bonds of the Japan-US alliance the Japan-US Security Treaty and the search for mutuality - Sakamoto, Kazuya 1956-; Nihon Kokusai Mondai Kenkyu?jo (2022)
The Japan-US Security Treaty was first signed in 1951, coinciding with the end of Allied occupation and Japan's recovery of independence in the early postwar era, and subsequently revised in 1960 to correct various inadequacies and alleviate a sense of inequality felt on the Japanese side. Its basic structure, namely providing bases in exchange for the guarantee of US security of Japan, however, remains unchanged. Drawing on previously undisclosed confidential documents and new research developments on the issue of secret agreements which were brought to light during the Ministry of Foreign Affairs investigation in 2009-10, the author carefully depicts the sensitive negotiations and diplomatic finesse behind the establishment and revision of the Japan-US Security Treaty, highlighting the challenges experienced by the two countries to promote mutuality then and later, and adding a new chapter with updated notes for his revised 2020 edition. Examining the far-reaching implications of these new historical materials, he puts forward the pressing question: What should be the future of Japan-US security cooperation?
Documents Security treaty between Japan and the United States of America (former US-Japan Security Treaty) -- Notes exchanged between Prime Minister Yoshida and Secretary of State Acheson at the time of the signing of the security treaty between Japan and the United States of America -- Treaty of mutual cooperation and security between Japan and the United States of America -- Exchanged notes, regarding the implementation of Article VI of Treaty of Mutual Cooperation and Security between Japan and the United States of America -- Exchanged notes, regarding exchanged notes between Prime Minister Yoshida and Secretary of State Acheson. -- Chronology -- References Primary sources Books Papers and book chapters, etc. Periodicals -- Index -- About the author.
"This English edition includes additional revisions to the 2020 revised Japanese edition for purposes of readability. These include, but are not confined to, the incorporation of the original supplementary notes into chapter endnotes and the conversion of the original Addendum into a new Chapter 6."--Title page verso.
Revised and expanded English edition of diplomatic historian Sakamto Kazuya's highly acclaimed Nichi-Bei domei no kizuna (The Bonds of the Japan-US Alliance; 2000, revised edition 2020), winner of the 22nd Suntory Prize for Social Sciences and Humanities.
Includes bibliographical references (pages 372-382) and index.
Keywords: Treaty of Mutual Cooperation and Security between the United States of America and Japan -- (1960 January 19).; Military assistance, American -- Japan; Assistance militaire ame?ricaine -- Japon; Japan -- Defenses; United States -- Military relations -- Japan; Japan -- Military relations -- United States; Etats-Unis -- Relations militaires -- Japon